2007
DOI: 10.1007/s11524-007-9195-1
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and Stroke Prevalence in Taiwan: Analysis of a Nationwide Survey

Abstract: This study aims to explore the prevalence of strokes among individuals and the association with urbanization levels. A total sample of 9,794 individuals was obtained from a nationwide survey on Taiwan for subsequent analysis in this study. After adjusting for gender, age, other risk factors for stroke and individual socioeconomic status, a multivariate logistic regression model was employed to investigate the relationships existing between the prevalence of strokes and the level of urbanization. This study fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 38 publications
2
56
3
Order By: Relevance
“…A widespread skepticism prevails regarding the validity of diagnostic coding in medical claims, but previous epidemiological studies conducted with the LHID have revealed results consistent with population-based surveys for several conditions. (38) Furthermore, to maximize diagnostic coding accuracy in medical claims, the NHI has extensive and systemic qualityassurance processes including routine crosschecking of chart reviews by clinical specialists. Because cardiovascular events such as myocardial infarction and stroke are critical illnesses causing severe disability, almost all patients need medical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A widespread skepticism prevails regarding the validity of diagnostic coding in medical claims, but previous epidemiological studies conducted with the LHID have revealed results consistent with population-based surveys for several conditions. (38) Furthermore, to maximize diagnostic coding accuracy in medical claims, the NHI has extensive and systemic qualityassurance processes including routine crosschecking of chart reviews by clinical specialists. Because cardiovascular events such as myocardial infarction and stroke are critical illnesses causing severe disability, almost all patients need medical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, epidemiological studies conducted with the LHID have yielded results that are consistent with population-based surveys for several conditions. 36 Therefore, the reliability of diagnostic coding in medical claims is considered acceptable for epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Several studies in India have demonstrated a higher prevalence of NCD risk factors in urban than in rural areas. [18][19][20][21][22] Epidemiological studies have shown that in rural adults, the prevalence of coronary heart disease is lower (3-5%) than in urban adults (7-10%).…”
Section: Discussionmentioning
confidence: 99%